Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques